Analisis terhadap Kontribusi Pajak Reklame, Pajak Hotel dan Pajak Restoran dalam Meningkatkan Pendapatan Asli Daerah (PAD) pada Badan Pendapatan Daerah DKI Jakarta - Inda Irmanda Safitri (Jurnal Manajemen, 2021)
This study aims to determine the contribution of advertisement tax, hotel tax and restaurant tax in increasing local revenue (PAD) in the Regional Revenue Agency of DKI Jakarta Province. The research design used in this study is to use quantitative descriptive methods. Data collection techniques using library research, documentation and observation. The results of this study indicate that the average contribution in 2015-2019 of the Advertising Tax is 2.30%, meaning that the average level of contribution is sufficient to have a contribution. The average contribution rate of Hotel Tax in 2015-2019 is 3.86%, which means that the average level of contribution has contributed. The average contribution rate of Restaurant Tax in 2015-2019 is 6.98%, which means that the average level of contribution is very significant. The average contribution rate of Advertising Tax, Hotel Tax and Restaurant Tax in 2015-2019 is 13.13%, which means that the average level of contribution greatly contributes. Keywords: Advertisement Tax, Hotel Tax, Restourant Tax